The Use of Urban Plazas - Mohamed, Noorizan (1992)
In Malaysia, factors that contribute toward plaza use have not yet been identified. A pilot study to determine some of the factors that affect plaze use was conducted at five plazas in Kuala Lumpur and Petaling Jaya. Observation of each plaza was carned out and simple counts of the number of users within the boundaries of the plazas were taken. Mean use was determined and correlated with physical characteristics of the plaza and contextual characteristics of the surrounding area using Pearson Correlation Coefficient. Study data showed that plazas with more shaded seating, more plants and located close to retail stores, restaurants and surface parking tended to be heavily used. Plazas which were hidden or had a parking garage tended to be used less. Future studies need to be more intensive and refined in order to validate these findings